2021
DOI: 10.3390/pharmaceutics13040549
|View full text |Cite|
|
Sign up to set email alerts
|

Challenges in the Physical Characterization of Lipid Nanoparticles

Abstract: Nano-sized drug transporters have become an efficient approach with considerable commercial values. Nanomedicine is not only limited to drug delivery by means of different administration routes, such as intravenous, oral, transdermal, nasal, pulmonary, and more, but also has applications in a multitude of areas, such as a vaccine, antibacterial, diagnostics and imaging, and gene delivery. This review will focus on lipid nanosystems with a wide range of applications, taking into consideration their composition,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 70 publications
(39 citation statements)
references
References 178 publications
1
38
0
Order By: Relevance
“…The viability of cells treated with charged liposomes was slightly higher than those treated with plain-LP. This effect could be ascribed to the possible electrostatic repulsion between the negative charge and the membrane macromolecules, leading to a reduced cell-liposome interaction with a subsequent reduction in the LP antiproliferative effect [49,50].…”
Section: In Vitro Effect Of Produced Liposomal Formulations On Cultur...mentioning
confidence: 99%
“…The viability of cells treated with charged liposomes was slightly higher than those treated with plain-LP. This effect could be ascribed to the possible electrostatic repulsion between the negative charge and the membrane macromolecules, leading to a reduced cell-liposome interaction with a subsequent reduction in the LP antiproliferative effect [49,50].…”
Section: In Vitro Effect Of Produced Liposomal Formulations On Cultur...mentioning
confidence: 99%
“…For example, none of the nanocarriers associated with CPPs have so far been approved for clinical studies. Evidently, besides overcoming membrane barriers, a string of challenges remain that need to be tackled for peptide nanocarriers to make a breakthrough in clinical application whereas lipid-based formulations, for all their drawbacks [277], are being used in the field of gene therapy and as a delivery vehicle in mRNA-based vaccines [278]. Short circulation half-lives, inadequate biodistribution, and poor chemical and physical serum stability, especially susceptibility to proteolytic degradation associated with off-target nucleic acid release, hamper clinical translation of peptide-based nanocarriers.…”
Section: Discussionmentioning
confidence: 99%
“…Among lipid nanoparticles, solid lipid nanoparticles (SLNs) and nanostructured lipid carriers (NLCs) are colloidal carriers exploiting many effects on skin, and therefore are suitable for skin applications. Figure 5 shows exemplary cryo-TEM images of tristearin SLNs (c) and NLCs (d) [ 99 , 100 , 101 ]. It has been demonstrated that the solid core of these nanoparticles is able to better sustain and control the release of drug as compared to emulsions or other vesicles, such as liposomes [ 96 ].…”
Section: Lipid-based Nanosystemsmentioning
confidence: 99%